A New Approach to Estimating Equilibrium Models for Metropolitan Housing Markets - Epple, Dennis; Quintero, Luis; Sieg, Holger (Journal of Political Economy, 2020)
We provide a new estimator for a broad class of equilibrium models of metropolitan housing markets with housing differentiated by quality. Quality is a latent variable that captures all features of a dwelling and its environment. We estimate the model for Chicago and New York, obtaining hedonic housing price functions for each quality level for each metropolitan area, stocks of each quality, and compensating variations required for a household of a given income in Chicago to be equally well off in New York.